(x^2+1)^2-(x^2-5)^2
(4x^2-25)^2-(2x-5)^2 help
1.
(x^2 +1)^2 -(x^2 -5)^2 =
= x^4 + 2x^2 +1 -(x^4 -10x^2 + 25) =
= x^4 + 2x^2 +1 - x^4 +10x^2 - 25 =
= 12x^2 - 24 =
= 12(x^2 - 2)
2.
(4x^2 - 25)^2 -(2x -5)^2 =
= [(2x+5)(2x-5)]^2 -(2x-5)^2 =
= (2x+5)^2 *(2x-5)^2 -(2x-5)^2 =
=(2x-5)^2 * [(2x+5)^2 -1] =
=(2x-5)^2 *(4x^2 +20x+25-1) =
=(2x-5)^2 *(4x^2 +20x +24)=
=(2x-5)^2 * 4(x^2 +5x+6) =
= 4(2x-5)^2 *(x+2)(x+3)
" Life is not a problem to be solved but a reality to be experienced! "
© Copyright 2013 - 2025 KUDO.TIPS - All rights reserved.
1.
(x^2 +1)^2 -(x^2 -5)^2 =
= x^4 + 2x^2 +1 -(x^4 -10x^2 + 25) =
= x^4 + 2x^2 +1 - x^4 +10x^2 - 25 =
= 12x^2 - 24 =
= 12(x^2 - 2)
2.
(4x^2 - 25)^2 -(2x -5)^2 =
= [(2x+5)(2x-5)]^2 -(2x-5)^2 =
= (2x+5)^2 *(2x-5)^2 -(2x-5)^2 =
=(2x-5)^2 * [(2x+5)^2 -1] =
=(2x-5)^2 *(4x^2 +20x+25-1) =
=(2x-5)^2 *(4x^2 +20x +24)=
=(2x-5)^2 * 4(x^2 +5x+6) =
= 4(2x-5)^2 *(x+2)(x+3)